Analysis of the Melting Time of Phase Change Material in a Heat Exchanger with Sinusoidal Inner Duct - Öztop, Hakan Fehmi; Akbal, Omer; Selimefendigil, Fatih; Abu-Hamdeh, Nidal H. (Mdpi, 2023)
Three-dimensional computational analysis has been performed to investigate the melting time of the phase change material (PCM) in a sinusoidal pipe inserted into another pipe. The other pipe is filled with PCM and the system is heated from the inner sinusoidal pipe at different temperatures. The main aim of the study is to control the melting time. The finite volume method (FVM) is used to solve time-dependent governing equations. Four different cases are chosen for the sinusoidal wall to see the effects of geometry on melting. After the analysis, it is observed that melting time can be controlled via an adjustment of the geometrical parameter, namely a passive technique, without spending extra energy.
Keywords: sinusoidal heat exchanger; phase change material; CFD; numerical; melting; heat transfer